2019
DOI: 10.1596/978-1-4648-1248-4
|View full text |Cite
|
Sign up to set email alerts
|

Exports to Jobs: Boosting the Gains from Trade in South Asia

Abstract: Th is work is a copublication of the World Bank and the International Labour Organization. Th e fi ndings, interpretations, and conclusions expressed in this work do not necessarily refl ect the views of Th e World Bank, its Board of Executive Directors, or the governments they represent, or those of the International Labour Organization. Th e World Bank and the International Labour Organization do not guarantee the accuracy of the data included in this work. Th e boundaries, colors, denominations, and other i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 51 publications
1
15
1
Order By: Relevance
“…As Indian import portfolio was majorly dependent of crude oil, therefore the import substitution policies in India has been able to reduce the import of crude oil and other petroleum products, and consequently, the level of CO 2 emissions. A recent report by World Bank (Artuc et al, 2019) has reflected this achievement by Indian government, and they have stressed on replicating this practice for the other Asian countries as a first stepping stone towards achieving the SDGs by 2030. On this ground, Ali and Abdullah (2015) found that trade intensification causes rise in the level of CO 2 emissions in Malaysia, whereas Hossain (2011) found the similar impact for Thailand, and Shahzad et al (2017) found the same for Pakistan.…”
Section: Ivi Long-run Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Indian import portfolio was majorly dependent of crude oil, therefore the import substitution policies in India has been able to reduce the import of crude oil and other petroleum products, and consequently, the level of CO 2 emissions. A recent report by World Bank (Artuc et al, 2019) has reflected this achievement by Indian government, and they have stressed on replicating this practice for the other Asian countries as a first stepping stone towards achieving the SDGs by 2030. On this ground, Ali and Abdullah (2015) found that trade intensification causes rise in the level of CO 2 emissions in Malaysia, whereas Hossain (2011) found the similar impact for Thailand, and Shahzad et al (2017) found the same for Pakistan.…”
Section: Ivi Long-run Resultsmentioning
confidence: 99%
“…In such a scenario, in order to sustain the economic growth pattern, the policymakers are trying to bring amendments in the trade pattern, so that the dependence on imported natural resources can be reduced, while the domestic production can be given a boost to create employment. A recent report by World Bank (Artuc et al, 2019) states that India might set an example for the South Asian economies the envisaging import substitution policies as a mean to achieve sustainable development. Based on this discussion, India can be considered as a case study for the South Asian and Asia Pacific economies in their endeavors to achieve the SDG objectives, and the learnings for the Indian context can be utilized in these nations.…”
Section: Introductionmentioning
confidence: 99%
“…This sector is associated with lower productivity and weaker access to finance, a barrier to productive investment and a constraint on firms. Encouraging participation in GVCs and enhancing a businessfriendly regulatory and tax environment can promote resource reallocation from less productive informal activities to more productive formal ones in SAR (Amin, Ohnsorge, and Okou 2019;Artuc et al 2019).…”
Section: Enhancing Firm Productivitymentioning
confidence: 99%
“…In this respect, South Asian countries are required to strive more to integrate into global markets (Mahmood and Ahmed, 2017) in order maintain its ascending progress trajectory. It is also propagated that this would not also create more employment in these economies (Brooks and Go, 2012) yet also up lift the well-being of people (Artuc et al, 2019).…”
Section: Currency Depreciation and Exports: A Recent South Asian Contextmentioning
confidence: 99%